Evaluating Safety and Effectiveness of Switching Biologics in Managing Severe Asthma Patients - Al Awn L; AlAmmari M; AlAbdulkarim D; AlAhmed R; Yadav B; AL-Jahdali H (Journal of Asthma and Allergy)
Leena Al Awn,1– 3 Maha AlAmmari,1– 3 Dalal AlAbdulkarim,1– 3 Reem AlAhmed,3– 5 Bijesh Yadav,3,5 Hamdan AL-Jahdali3– 5 1Department of Pharmaceutical Care Services, King Abdulaziz Medical City (KAMC), Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 2College of Pharmacy, King Saud bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh, Saudi Arabia; 3King Abdullah International Medical Research Center (KAIMRC), Riyadh, Saudi Arabia; 4Department of medicine, King Abdulaziz Medical City (KAMC), Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 5College of Medicine, King Saud bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh, Saudi ArabiaCorrespondence: Leena Al Awn, Email leena7ibraheem@gmail.comBackground: The Saudi Initiative for Asthma (SINA) defines severe asthma as asthma that is uncontrolled at SINA step 4 despite optimized management. Choosing the biologic agent that is most appropriate for each patient can be difficult for clinicians. Thus, switching to another biologic agent due to no or suboptimal response is a common practice among asthma specialists. Therefore, this study aims to evaluate the safety and efficacy of switching biologics in patients with severe asthma at a tertiary care center.Methods: This was an observational retrospective cohort single-center study conducted at King Abdulaziz Medical City-Central Region, Riyadh, Saudi Arabia. All adult patients ≥ 18 years of age with a confirmed diagnosis of severe asthma and who were switched from one biologic agent (omalizumab, mepolizumab and dupilumab) to another were included.Results: Thirty-three patients were included in the final analysis. In the majority of patients (81%), switching occurred due to lack of clinical efficacy. Most patients were maintained on the first and second biologic for 6 months or more. Most switching occurred from omalizumab to mepolizumab and dupilumab was the most frequently used last-line biologic (54%). Compared to the first biologic, the mean number of exacerbations decreased after switching to a different biologic (6.6 vs 3.9, p = 0.1). On the other hand, sinus symptoms improved after patients were switched to a different biologic (18.5% vs 37.5%, p = 0.1).Conclusion: Switching from one biologic agent to another is effective and safe in patients who are not optimally controlled on the initial treatment. National and international guidelines should define and include criteria for switching biologics.Keywords: asthma, biologics, switching, effectiveness, safety